Netherlands : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1995)
This paper describes economic developments in Kingdom of the Netherlands-Aruba during the 1990s. During 1993-94, Aruba's economic expansion continued at a brisk pace, albeit somewhat slower than the very high rates of growth attained during the late 1980s. Growth was mainly supported by private domestic demand, with both the consumption and investment components contributing significantly, while the contribution of the external sector turned negative. This strong growth in domestic demand exacerbated the already severe supply constraints of the Aruban economy, resulting in very tight labor market conditions and an acceleration of inflation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet